2002
DOI: 10.1046/j.1462-2920.2002.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Escherichia coli O157:H7 in soil and on plant roots

Abstract: Soil microcosms were inoculated with Escherichia coli O157:H7 to test persistence in fallow soil, on roots of cover crops and in presence of manure. In fallow soils, E. coli O157:H7 persisted for 25-41 days, on rye roots for 47-96 days and on alfalfa roots, in a silt loam soil, for 92 days whereas on other legumes persistence ranged from 25-40 days, similar to fallow soil. Manure did not seem to affect the persistence of E. coli O157:H7 in these soils. Indigenous and manure-applied coliform populations often d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 18 publications
5
91
2
Order By: Relevance
“…These results indicate that lettuce grown in soil containing Salmonella or E. coli O157:H7 may become contaminated throughout the growing season. Gagliardi and Karns (2002) revealed that E. coli O157:H7 survived for 25 to 41 days in fallow Table 4. Effects of mulching and surface disinfection on Salmonella counts of lettuce cultivated in highly contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that lettuce grown in soil containing Salmonella or E. coli O157:H7 may become contaminated throughout the growing season. Gagliardi and Karns (2002) revealed that E. coli O157:H7 survived for 25 to 41 days in fallow Table 4. Effects of mulching and surface disinfection on Salmonella counts of lettuce cultivated in highly contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…A good example is the enterohemorrhagic strain E. coli O157:H7 that can be internalized into lettuce when exposed to contaminated irrigation water or soil (Solomon et al, 2002;Wachtel et al, 2002). Moreover, because plants are privileged hosts for these bacteria, if supplied in irrigation water, they can proliferate and survive for longer periods when plants are present than in their absence (Gagliardi and Karns, 2002;Ibekwe et al, 2004;Tyler and Triplett, 2008). Another risk is that bacteria transmitted by this pathway may be inherited through plant seeds, as has been described for some endophytic bacteria (Burnett et al, 2000;Cooley et al, 2003;Guo et al, 2001;Rosenblueth and Martínez-Romero, 2006;Tyler and Triplett, 2008;Wang et al, 2006).…”
Section: Risk Of Dissemination Of Pathogens Through Wastewater Reusementioning
confidence: 99%
“…Persistence of STEC in the soil [55,56] favours the infection of cattle and makes environmental exposure a risk factor for human infection [32,75,125,158]. Animal wastes and effluents from farming operations, including manure and slurries, are frequently applied as a fertiliser to land used for crop or silage production and cattle grazing.…”
Section: Persistence In Faeces and Manurementioning
confidence: 99%